Who Is More Dangerous? Comparing the Criminality of Adult Homeless and Domiciled Jail Inmates: A Research Note - DeLisi, Matt (International journal of offender therapy and comparative criminology, 2000)
The criminality of 100 homeless and 100 domiciled jail inmates was compared. Homeless jail inmates were significantly more likely than domiciled jail inmates to be mentally ill, to be arrested for nuisance offenses, to have more extensive criminal histories, and to have prior arrests for use of weapons, drugs, and alcohol. Suggestions for processing homeless offenders are given